Tax and Zakat According to Islamic Law: The Civil Servants' Obligation in Fulfilling Social Responsibility - Muhammadong Muhammadong (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Tax and zakat are two important duties that are very important for keeping the country and society going. In Indonesia, both positive law and Islamic law say that civil servants (PNS) have a social duty to meet certain tasks. This paper seeks to examine the responsibilities of PNS in discharging both tax and zakat commitments from the viewpoint of Islamic law, which stipulates that every individual is required to pay both to enhance societal welfare. The aim of this study is to delineate and examine the responsibilities of PNS regarding the payment of taxes and zakat, alongside the Islamic legal viewpoint on both. Data was gathered through a qualitative methodology employing descriptive analysis from both primary and secondary sources, including legislation, fatwas, and pertinent literature. The study's results show that, according to Islamic law, tax is a legal duty of the state, but zakat is a religious duty that all Muslims, including PNS, must undertake. These two duties work together to improve the well-being of society. Because of this, PNS has a double duty to pay taxes and zakat: it is both a state duty and a social duty under Islamic law.